2019
DOI: 10.1136/bmjopen-2017-020554
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with paediatric unplanned hospital readmissions: a systematic review

Abstract: ObjectiveTo synthesise evidence on risk factors associated with paediatric unplanned hospital readmissions (UHRs).DesignSystematic review.Data sourceCINAHL, EMBASE (Ovid) and MEDLINE from 2000 to 2017.Eligibility criteriaStudies published in English with full-text access and focused on paediatric All-cause, Surgical procedure and General medical condition related UHRs were included.Data extraction and synthesisCharacteristics of the included studies, examined variables and the statistically significant risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 109 publications
2
41
0
Order By: Relevance
“…This retrospective cohort study used historical data from 2010 to 2014, which may reduce the relevance to current clinical practice. However, risk factors associated with paediatric unplanned hospital readmissions have remained stable over the last decade, based on our recently published systematic review, 1 indicating that the datasets used in this study provided relevant information regarding current readmission factors.…”
Section: Clinicalmentioning
confidence: 86%
See 1 more Smart Citation
“…This retrospective cohort study used historical data from 2010 to 2014, which may reduce the relevance to current clinical practice. However, risk factors associated with paediatric unplanned hospital readmissions have remained stable over the last decade, based on our recently published systematic review, 1 indicating that the datasets used in this study provided relevant information regarding current readmission factors.…”
Section: Clinicalmentioning
confidence: 86%
“…The identification of predictive factors associated with paediatric unplanned readmission to hospital can be used to improve discharge planning processes, and thereby help prevent such readmissions. Prior research has uncovered many of these factors; a recent systematic review 1 of the existing literature extracted 36 unique predictors associated with paediatric unplanned hospital readmissions from 44 studies. The most commonly cited four predictors were comorbidity, health insurance status, length of stay (LOS), and age at the index admission.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to findings from this study, which identified that patients older than 13 years were nearly 1.5 times more likely to be readmitted compared with younger patients. This may be related to adolescents and young adults with underlying chronic health conditions Further research is recommended to examine whether, potentially, some unplanned hospital readmissions may be unavoidable due to medical complexity…”
Section: Discussionmentioning
confidence: 99%
“…Unplanned hospital readmission rate has been widely accepted as a service performance indicator to evaluate the quality of health‐care delivery . A recent systematic review examined research evidence on paediatric unplanned hospital readmissions from 2000 to 2017. Some American studies used 365 days to measure the all‐cause unplanned readmissions, and the prevalence was from 16.7 to 21.8% .…”
mentioning
confidence: 99%
“…discharge planning, transition of care between inpatient and outpatient providers), but have not been endorsed to date for neonatal care, primarily because of a lack of agreement between study teams of what constitutes “preventable” readmissions. 1 , 2 , 3 , 4 , 5 Readmissions and emergency department visits of very premature, moderate preterm, late preterm, and early term infants have been studied by many investigators. 6 , 7 , 8 However, term infants account for many readmissions, for they comprise the majority (~90%) of live births, but readmissions of term infants have not been as well studied.…”
Section: Introductionmentioning
confidence: 99%